2018
DOI: 10.1002/anie.201808764
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Functionalization of Enamides at the β‐Carbon Center with Indoles

Abstract: We report an enantioconvergent approach for the functionalization of enamides at the β-carbon atom, which involves a chiral Brønsted acid induced tautomerization of 2-amidoallyl into 1-amidoallyl cations. These putative reactive intermediates were produced by ionization of racemic α-hydroxy enamides with a chiral Brønsted acid and captured with substituted indoles in a highly regio- and enantioselective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…With similar research interests, Kartika and co-workers also reported parallel work on asymmetric additions of indoles to α-hydroxy cyclopentenamides catalyzed by chiral phosphoric acids, at the same time as our work was published. 15 Compared with our results, they obtained better reaction outcomes for α-alkyl-substituted enamides (Scheme 8). Their substrate-scope studies also demonstrated that various substituted indoles were well tolerated under the optimal conditions (10 mol% cat B, DCE, -10 °C), whereas α-methyl or α-aryl substitution gave the β-indolyl cyclopentenamides 9 with high enantioselectivities (9a-d).…”
Section: Scheme 7 Further Transformations Of 3acontrasting
confidence: 54%
“…With similar research interests, Kartika and co-workers also reported parallel work on asymmetric additions of indoles to α-hydroxy cyclopentenamides catalyzed by chiral phosphoric acids, at the same time as our work was published. 15 Compared with our results, they obtained better reaction outcomes for α-alkyl-substituted enamides (Scheme 8). Their substrate-scope studies also demonstrated that various substituted indoles were well tolerated under the optimal conditions (10 mol% cat B, DCE, -10 °C), whereas α-methyl or α-aryl substitution gave the β-indolyl cyclopentenamides 9 with high enantioselectivities (9a-d).…”
Section: Scheme 7 Further Transformations Of 3acontrasting
confidence: 54%
“…In recent decades, the asymmetric catalysis through the formation of a chiral ion pair, especially with the chiral phosphoric acids, , has been termed as asymmetric counteranion-directed catalysis (ACDC) by List et al, and versatile advances have been disclosed by List, Toste, Jacobsen, and others. , Inspired by these advances and in continuation of our interest in transition metal/chiral phosphoric acid cooperatively catalyzed asymmetric multicomponent reactions (MCRs), we became interested in the chiral-counteranion-directed asymmetric aminomethylation of 3-indolyloxindole . We hypothesize that the in situ generated chiral methylene iminium ion IV from N , O -acetals in the presence of a chiral Brønsted acid might intercept the zwitterionic intermediate V that is derived from 3-diazooxindole and indole catalyzed by a dirhodium complex (Path F).…”
mentioning
confidence: 99%
“…Recently, the combination of 2‐amidoallylic alcohol substrates (or “α‐hydroxy enamides”) with chiral Brønsted acid catalysis has become a useful strategy for the asymmetric synthesis of functionalized enamide derivatives . Our group and Kartika and co‐workers independently reported the asymmetric synthesis of β‐indolyl cyclopentenamides from α‐hydroxy cyclopentenamides by chiral phosphoric acid catalysis (Figure a). On the other hand, Chan and co‐workers reported a dehydrative Nazarov‐type electrocyclization of α‐hydroxy enamides that provides access to chiral 1 H ‐indene derivatives under chiral Brønsted acid catalysis (Figure b).…”
Section: Figurementioning
confidence: 99%